2011
DOI: 10.1016/j.ijgo.2011.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Etoposide, cisplatin–etoposide, methotrexate, actinomycin‐D as primary treatment for management of very‐high‐risk gestational trophoblastic neoplasia

Abstract: EP-EMA was highly effective for the primary management of very-high-risk GTN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…• EMA/EP (etoposide, methotrexate, dactinomycin alternating with etoposide and cisplatin) 65,66 or EP/ EMA (etoposide and cisplatin alternating with etoposide, methotrexate, and dactinomycin) 67 • MEA (methotrexate, etoposide, dactinomycin) 68 • MAC (methotrexate, dactinomycin, and chlorambucil) 69 • FA (5-FU and dactinomycin) 70 • MEF (methotrexate, etoposide, and 5-FU) 71 • CHAMOCA (methotrexate, dactinomycin, cyclophosphamide, doxorubicin, melphalan, hydroxyurea, and vincristine) 69 Due to the lack of RCTs in this setting, systematic reviews have been unable to draw conclusions regarding a superior combination regimen for primary treatment of high-risk GTN. 46,72 EMA/EP (or EP/EMA) is highly active and considered by some to be superior to EMA/CO for ultra-high-risk disease; however, its use as standard initial therapy is limited by increased toxicity and inability to provide adequate salvage chemotherapy if required for persistent/recurrent disease.…”
Section: High-risk Gtnmentioning
confidence: 99%
“…• EMA/EP (etoposide, methotrexate, dactinomycin alternating with etoposide and cisplatin) 65,66 or EP/ EMA (etoposide and cisplatin alternating with etoposide, methotrexate, and dactinomycin) 67 • MEA (methotrexate, etoposide, dactinomycin) 68 • MAC (methotrexate, dactinomycin, and chlorambucil) 69 • FA (5-FU and dactinomycin) 70 • MEF (methotrexate, etoposide, and 5-FU) 71 • CHAMOCA (methotrexate, dactinomycin, cyclophosphamide, doxorubicin, melphalan, hydroxyurea, and vincristine) 69 Due to the lack of RCTs in this setting, systematic reviews have been unable to draw conclusions regarding a superior combination regimen for primary treatment of high-risk GTN. 46,72 EMA/EP (or EP/EMA) is highly active and considered by some to be superior to EMA/CO for ultra-high-risk disease; however, its use as standard initial therapy is limited by increased toxicity and inability to provide adequate salvage chemotherapy if required for persistent/recurrent disease.…”
Section: High-risk Gtnmentioning
confidence: 99%
“…The overall cure rate was 96.4%, with a mortality of 0.4% for low-risk disease, 9.5% for high-risk and 21.4% for PSTT 7 . Methotrexate (MTX), actinomycin-D (ActD), cyclophosphamide, vincristine, etoposide, cisplatin and paclitaxel are some of the drugs used to treat GTN effectively 19 . After hCG returns to normal levels, additional ChT courses, called consolidation ChT, are repeated three to four times, especially in cases of high-risk disease, to avoid recurrence 20 .…”
Section: Treatmentmentioning
confidence: 99%
“…Type of GTN pathology was unknown in most patients ( Table 2 ). Uterine mass was detected in 16 of 20 patients (84%), and tumor size was less the 5 cm in 52% of the cases ( 11 ). Four patients underwent hysterectomy, of which 3 had the tumor size of greater than 5 cm.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the higher response rate of EMA/EP, compared to EMA/CO, some authors have suggested EMA/EP as the first- line chemotherapy regimen ( 11 ). EMA/EP has been used as a good salvage treatment with a survival rate of up to 84.9% ( 8 ).…”
Section: Introductionmentioning
confidence: 99%